2021
DOI: 10.3390/nu13051527
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Selenium Regulates microRNAs in Metabolic Disease: Recent Progress

Abstract: Selenium (Se) is an essential element for the maintenance of a healthy physiological state. However, due to environmental and dietary factors and the narrow safety range of Se, diseases caused by Se deficiency or excess have gained considerable traction in recent years. In particular, links have been identified between low Se status, cognitive decline, immune disorders, and increased mortality, whereas excess Se increases metabolic risk. Considerable evidence has suggested microRNAs (miRNAs) regulate interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 129 publications
(131 reference statements)
0
6
0
Order By: Relevance
“…Notably, our results indicated a significant reduction in miR-21 levels not only in response to a generally healthy diet but also, more specifically, upon analysing the consumption of fruits and vegetables. A healthy dietary pattern has the potential to modulate miRNA activity through various pathways: bioactive compounds such as resveratrol, curcumin, quercetin, and catechins as well as minerals or vitamins and polyunsaturated fatty acids (PUFAS) have been reported to directly modulate miRNA expression [ 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. For instance, eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids as well as polyphenols exert part of their anti-inflammatory action by downregulating miRNAs like miR-146a, miR-21, and miR-155, particularly after macrophage and epithelial cell stimulation while mediating NF-κB signalling [ 64 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our results indicated a significant reduction in miR-21 levels not only in response to a generally healthy diet but also, more specifically, upon analysing the consumption of fruits and vegetables. A healthy dietary pattern has the potential to modulate miRNA activity through various pathways: bioactive compounds such as resveratrol, curcumin, quercetin, and catechins as well as minerals or vitamins and polyunsaturated fatty acids (PUFAS) have been reported to directly modulate miRNA expression [ 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. For instance, eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids as well as polyphenols exert part of their anti-inflammatory action by downregulating miRNAs like miR-146a, miR-21, and miR-155, particularly after macrophage and epithelial cell stimulation while mediating NF-κB signalling [ 64 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selenate is reduced to selenite prior to further metabolism, and this reduction process is catalyzed by selenate and selenite reductases. [91][92][93] Avazeri et al found that nitrate reductases A and Z can reduce selenite to selenate. [93] Meanwhile, Se (IV) reacts with the reduced GSH to generate selenodiglutathione (GS-Se-SG).…”
Section: Mechanism Of Se Enrichment By Probioticsmentioning
confidence: 99%
“…Alternatively, epigenetic mechanisms within developing offspring may also explain developmental programming responses resulting from dietary Se supplementation ( 53 ). Specifically, enzymes associated with one-carbon metabolism have been shown to be affected by Se ( 54 , 55 ), while others ( 56 ) reported that Se regulates microRNAs ( 56 ) and DNA methylation ( 55 , 57 ). In humans experiencing Kashin-Beck disease (associated with Se deficiencies), differentially methylated genes were reported ( 53 ).…”
Section: Selenium Supplementation During Pregnancymentioning
confidence: 99%